High parasite diversity in the amphipod Gammarus lacustris in a subarctic lake. Issue 21 (5th October 2020) - Shaw, Jenny C.; Henriksen, Eirik H.; Knudsen, Rune; Kuhn, Jesper A.; Kuris, Armand M.; Lafferty, Kevin D.; Siwertsson, Anna; Soldánová, Miroslava; Amundsen, Per‐Arne
Abstract: Amphipods are often key species in aquatic food webs due to their functional roles in the ecosystem and as intermediate hosts for trophically transmitted parasites. Amphipods can also host many parasite species, yet few studies address the entire parasite community of a gammarid population, precluding a more dynamic understanding of the food web. We set out to identify and quantify the parasite community of Gammarus lacustris to understand the contributions of the amphipod and its parasites to the Takvatn food web. We identified seven parasite taxa: a direct life cycle gregarine, Rotundula sp., and larval stages of two digenean trematode genera, two cestodes, one nematode, and one acanthocephalan. The larval parasites use either birds or fishes as final hosts. Bird parasites predominated, with trematode Plagiorchis sp. having the highest prevalence (69%) and mean abundance (2.7). Fish parasites were also common, including trematodes Crepidostomum spp., nematode Cystidicola farionis, and cestode Cyathocephalus truncatus (prevalences 13, 6, and 3%, respectively). Five parasites depend entirely on G. lacustris to complete their life cycle. At least 11.4% of the overall parasite diversity in the lake was dependent on G. lacustris, and 16% of the helminth diversity required or used the amphipod in their life cycles. These dependencies reveal that in addition to being a key prey item in subarctic lakes, G. lacustris is also an important host for maintaining parasite diversity in such ecosystems. Abstract : We set out to identify and quantify the parasite community of Gammarus lacustris to understand the contributions of the amphipod and its parasites to the Takvatn food web. We identified seven parasite taxa: a direct life cycle gregarine, Rotundula sp., and larval stages of two digenean trematode genera, two cestodes, one nematode, and one acanthocephalan. We found that G. lacustris is not only a key prey item in subarctic lakes, it is also an important host for maintaining parasite diversity in such ecosystems.